Tissue Targeting and Ultrasound-Targeted Microbubble Destruction Delivery of Plasmid DNA and Transfection In Vitro - Wang, Yue (Cell Mol Bioeng, 2019)
INTRODUCTION: Ultrasound-targeted microbubble destruction (UTMD) has been shown a promising approach for target-specific gene delivery and treatment of many diseases in the past decade. To improve the therapeutic potential of UTMD, the gene carrier of microbubbles should possess adequate DNA condensation capability and (or) specific cell or tissue selectivity. The tissue-targeted and ultrasound-targeted cationic microbubbles were developed to meet gene therapy. METHODS: A tissue-targeted stearic acid-inserted cationic microbubbles (SCMBs) were prepared for ultrasound-targeted gene delivery. Branched PEI was modified with stearic acid and further mixed with 1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC) and biot-1,2-distearoyl-sn-glycero-3-phosphoethanolamine-N-[methoxy (polyethylene glycol)-2000] (ammonium salt) (Biot-DSPE-PEG2000), intercellular adhesion molecule-1 (ICAM-1) antibody and plasmid DNA to prepare cationic microbubbles through ultrasonic hydration. The ICAM-1 antibody and plasmid DNA were expected to assemble to the surface of SCMBs via biotin-avidin interaction and electrostatic interaction, respectively. RESULTS: It was found that the SCMBs had higher zeta potential compared with neutral microbubbles (NMBs) and cationic microbubbles (CMBs). In contrast, DNA incorporated SCMBs4 showed negative potential, exhibiting good DNA-binding capacity. Confocal images showed that the HeLa cells were attached around by the SCMBs4 from the view of green fluorescence of fluorescein isothiocyanate-loaded IgG which conjugated to ICAM-1 antibody on their surface. After ultrasound treatment, HeLa cells treated with SCMBs exhibited slightly stronger red fluorescence under confocal laser scanning microscope, indicating a synergistic promotion for transfection efficiency. CONCLUSIONS: This tissue- and ultrasound-targeted cationic microbubble demonstrated here showed a promising strategy for improving gene therapy in the future.